Ausländerrecht für japanische Staatsangehörige mit besonderem Augenmerk auf deren Erwerbstätigkeit im Bundesgebiet - Maiwald, Thorsten; Ott, Ulrich (Zeitschrift für Japanisches Recht, 2004)
Following their article on the German immigration laws in the No. 8 (1999) issue of the ZJAPANR / J.JAPAN.L., the authors now present an up-dated version of that contribution taking into account the important legal changes since 1999. The article first deals shortly with the legal frame of public international law, the immigration policy of the German Government, and the German immigration law. The authors, who both hold positions in the Ministry of the Interior of the Federal State of Baden-Württemberg, then give a very dense description of the relevance and consequences that the immigra-tion laws of the Federal Republic of Germany have for Japanese citizens. Special attention is given to the concession of working permits to Japanese nationals in Germany and the requirements that have to be fulfilled as well as the procedural steps for obtaining them. (The Editors)